My Image of the Unified Knowledge - E. V. Ryltsev (Интеллект. Инновации. Инвестиции)
The knowledge acquired by Mankind does not represent a single whole. Contradictions between religious and philosophical teachings and scientific theories exacerbate the already tense relations that, as a rule, develop between peoples, states and powerful organizations. The elimination of these contradictions is not a sufficient, but a necessary condition for building a just society on Earth, which will include all the peoples of the Earth. This task is very relevant for all progressive Mankind, has great practical significance. The purpose of the article is to contribute to the elimination of these contradictions. For thousands of years, the great minds of Mankind have strived to unite various parts of disparate knowledge. But Humanity is capable of building a Unified Knowledge – a system of knowledge composed of harmoniously connected true elements of religious and philosophical teachings and scientific theories created by all the peoples of the world throughout the history of Humanity. It should include the greatest religious ideas, the theory of knowledge, ontology, logic, fundamental ideas of physics, astronomy, chemistry, biology, geology and other similar important areas of knowledge. A special methodology is needed to build a Unified Knowledge. One of the options for such a methodology may be symphonics, the foundations of which were proposed by Daniil Valentinovich Pivovarov and his student, the author of this article. According to the author, in order to build a Unified Knowledge, one should strive to unite Christian and pagan teachings, mystical ideas about the structure of the World and classical ontology, ideas about the structure of matter in etherodynamics and ideas about particles of matter as living beings, achievements of modern astronomy and ancient astrology, achievements of modern chemistry and ancient alchemy, ideas about the evolution of the organic world and the Spiritual Hierarchy and other seemingly incompatible areas of knowledge. The main result of the article is the desire to unite the listed branches of knowledge into a single harmonious whole, which represents the scientific novelty of the study. The author of the article believes that in the future, a Unified Knowledge will be formed. This process will be very long. Many thousands of people will take part in such a grandiose work. But an individual is able to form in his consciousness a small part of the grandiose Unified Knowledge, its image. The author of the article offers such an image formed in his consciousness.